Semantic contrasts in phraseological units about work and idleness (based on study of Ukrainian, English and Spanish idioms) - Chernetska, N. (Studia Philologica, 2021)
The cross-cultural researches are becoming more relevant in the last decades. Due to these studies, scientists restore fragments of the linguistic picture of the world of particular nation, learn about rich historical heritage and customs of any nation, reveal its originality, define universal traits for cultures of different peoples and the peculiarities of different languages. The article is devoted to the complex research of phraseological units in the Ukrainian, Russian, English and Spanish languages. Interlinguistic relations are based on the structural and semantic aspects and it promotes identification of cultural peculiarities of phraseological units in these languages. Рhraseology is an integral and the richest part of any language. Studying materials were the Ukrainian, Russian, English and Spanish phraseological units related to the thematic group “work-idleness”. Equivalents of such phraseological units were analysed, as well as the sources of these equivalents, their types and methods of correct translation. The aim of the study is to identify national peculiarities in perception and verbal realization of one of the basic concepts, the “work-idleness” concept. It is achieved by comparing the Ukrainian with Russian, English and Spanish phraseological units. Full equivalents confirm the universality of this concept in Ukrainian, Russian, English and Spanish linguistic cultures. The article presents the comparative analysis of idioms with semantics of “work” — “inactivity, idleness, waste of time”; traced the basic models of idioms formation in different nations in various languages: Ukrainian, Russian, English and Spanish languages. It provides a new scientific in-depth approach to the solution of one of the most complex problems of comparative study of the phraseological material of different languages on the semantic level. Analysing the examples of phraseological units in different languages, the author comes to a conclusion that semantic, pragmatic, syntactic, national and cultural factors play a considerable role in the process of translation. These factors should be taken into account while translating idioms. So, the article deals with two concepts “work”, “idleness”. The subject of the research determines the application of the comparative method while investigating these two concepts in Ukrainian as well as in Russian, English and Spanish languages. The results of the present work can be applied in the sphere of such contiguous disciplines as intercultural communication, linguistics, translation theory and practice, studying English, Russian or Spanish by Ukrainian speaking students, as well as in writing test books and other teaching material on lexicology.